Cultivable Bacteria in Urine of Women With Interstitial Cystitis: (Not) What We Expected. Issue 5 (May 2021) - Jacobs, Kristin M.; Price, Travis K.; Thomas-White, Krystal; Halverson, Thomas; Davies, Abigail; Myers, Deborah L.; Wolfe, Alan J.
Abstract : Objective: Multiple studies show cultivatable bacteria in urine of most women. The existence of these bacteria challenges interstitial cystitis (IC)/painful bladder syndrome (PBS) diagnosis, which presumes a sterile bladder. The aims of this study were (1) to compare the female bladder microbiomes in women with IC/PBS and unaffected controls and (2) to correlate baseline bladder microbiome composition with symptoms. Methods: This cross-sectional study enrolled 49 IC/PBS and 40 controls. All provided catheterized urine samples and completed validated questionnaires. A subset of the IC/PBS cohort provided voided and catheterized urine samples. All samples from both cohorts were assessed by the expanded quantitative urine culture (EQUC) protocol; a subset was assessed by 16S rRNA gene sequencing. Results: Of the IC/PBS cohort, 49.0% (24/49) were EQUC positive; in these EQUC-positive samples, the most common urotypes were Lactobacillus (45.8%) and Streptococcus (33.3%). Of the controls, 40.0% were EQUC positive; of these EQUC-positive samples, the most common urotype was Lactobacillus (50.0%). The urotype distribution was significantly different ( P < 0.05), as 16% of the IC/PBS cohort, but 0% of controls, were Streptococcus urotype ( P < 0.01). Symptom-free IC/PBS participants were less likely to be EQUC positive (12.5%) than IC/PBS participants with moderate or severe symptoms (68.8% and 46.2%) and the control cohort (60%; P < 0.05). Conclusion: Lactobacillus was the most common urotype. However, the presence of Lactobacillus did not differ between cohorts, and it did not impact IC/PBS symptom severity. Bacteria were not isolated from most participants with active IC/PBS symptoms. These findings suggest that bacteria may not be an etiology for IC/PBS. Abstract : Supplemental digital content is available in the text.